Perspectives of Pre-Service English Teachers on AI Chatbots in ESP Worksheet Development - Savitri, Wiwiet Eva; Nugroho, Him'mawan Adi; Munir, Ahmad; Pusparini, Ririn; Kurniasih, Esti; Arinda, Desi (Universitas Pendidikan Mandalika, 2025)
The current existence of AI is unstoppable. Many parties consider AI to be a serious threat to the world of education, including universities. The use of AI by students in doing tasks often causes anxiety among lecturers. There is concern that AI reduces students’ creativity in exploring their own ideas in making essays or designing learning materials (worksheets). One of the courses that require students to explore their creativity is ESP Material Development. In this course, students are required to learn to develop teaching materials in the form of worksheets in accordance with the needs analysis results identified in the ESP Program Design course. This research is designed to find out students' tendencies in using AI for developing ESP worksheet, while also finding out whether they think that AI chatbot is really useful for them so that they can yield an ESP worksheet whose activities are in accordance with the learning objectives and having an attractive and professional appearance in the same time. The methods used were questionnaires for and FGD with 40 ESP Material Development class students. It was found that most students tried to use AI chatbot for getting inspiration whenever they get stuck in finding more ideas for their worksheets. Most students admitted that AI helped them in that situation. However, they did not recommend the use of AI from the very beginning of developing worksheets. They confessed that using AI would cause confusion and reduce creativity when it is used since very beginning.